Taming or Revering Nature? Equestrian Sports as Mirror of Nature Perceptions in the Early 20th Century - Steuerwald, Noemi (Idrott, historia och samhälle, 2026)
Few sports are as closely associated with nature as equestrianism. This article demonstrates how horses in the early 20th century served as a projection surface for conflicting ideas of nature: Nature as something that needed to be tamed and conquered, nature as an antithesis to modern and industrialized societies or nature as a commodity to be experienced through travel, tourism, and sport. These conceptualizations were closely intertwined with notions of gender, race, and class, reflecting the era’s complex relationship with nature. The article examines these negotiations as manifested in the treatment of horses as sporting and leisure animals in modernity. It further investigates how these perceptions shaped equestrian practices, from breeding to training methods. Studying historical sources, literature, and visual representations through the lens of historical discourse analysis, it becomes evident that equestrianism functioned as a cultural practice that both mirrored and shaped contemporary debates about nature, modernity, and power. The study thus highlights how the treatment of horses in sport and leisure was embedded in broader cultural efforts to define and negotiate the meaning of nature in an increasingly industrialized and stratified world.